2010
DOI: 10.1007/s00203-010-0558-8
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of ferric uptake regulator (fur) impair iron homeostasis, growth, oxidative stress survival, and virulence of Xanthomonas campestris pv. campestris

Abstract: Iron is essential in numerous cellular functions. Intracellular iron homeostasis must be maintained for cell survival and protection against iron's toxic effects. Here, we characterize the roles of Xanthomonas campestris pv. campestris (Xcc) fur, which encodes an iron sensor and a transcriptional regulator that acts in iron homeostasis, oxidative stress, and virulence. Herein, we isolated spontaneous Xcc fur mutants that had high intracellular iron concentrations due to constitutively high siderophore levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 54 publications
3
37
0
2
Order By: Relevance
“…Previous reports revealed that Fur is a critical cytoplasmic regulator of iron homeostasis in X . campestris as in other bacteria [16, 27]. Our study revealed that in X .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous reports revealed that Fur is a critical cytoplasmic regulator of iron homeostasis in X . campestris as in other bacteria [16, 27]. Our study revealed that in X .…”
Section: Discussionsupporting
confidence: 59%
“…campestris pv. campestris resulted in increased production of siderophores, reduced resistance to oxidative stress and decreased virulence [16]. Recently, a two-component signal transduction system, VgrR–VgrS (also named ColR-ColS), was identified as a canonical modulator controlling virulence of X .…”
Section: Introductionmentioning
confidence: 99%
“…Endpoint reverse transcription-PCR (RT-PCR) was carried out as previously described (31) to determine the expression level of tpx in P. aeruginosa under exposure to oxidative stress. Total RNA samples were isolated from the exponential-phase cultures of PAO1 induced with 250 M H 2 O 2 , CHP, menadione (MD), plumbagin (PB), or 100 M N-ethylmaleimide (NEM) for 20 min.…”
mentioning
confidence: 99%
“…Total RNA samples were isolated from the exponential-phase cultures of PAO1 induced with 250 M H 2 O 2 , CHP, menadione (MD), plumbagin (PB), or 100 M N-ethylmaleimide (NEM) for 20 min. The RT reaction was performed as described previously (31). After reverse transcription, the cDNA concentration was measured using a NanoDrop spectrophotometer.…”
mentioning
confidence: 99%
“…Bacterial cells from the unin- duced and NaOCl-induced cultures were collected. The total RNA was prepared and qRT-PCR was performed as described (Jittawuttipoka et al 2010). The reverse transcription reaction was conducted with a RevertAid TM M-MuLV Reverse Transcriptase kit (Fermentas) using random hexamers according to the manufacturer's recommendation.…”
Section: Real-time Reverse Transcription -Polymerase Chain Reaction (mentioning
confidence: 99%